(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2023)
The research aimed to determine the role of the quality of health services in its dimensions (tangibility, reliability, responsiveness, sympathy, and safety) in improving the performance of the health sector in private and public hospitals operating in Syria. Distribute a questionnaire to employees and clients of the hospitals under study. To test the hypotheses, the research relied on the method of regression analysis using the Amos-35 program, and concluded that there is a direct and significant effect of applying the dimensions of health services quality (tangibility, reliability, responsiveness, empathy, and safety) on improving the performance of the health sector in the hospitals under study. The research presented a set of recommendations, the most prominent of which were: the necessity of increasing the interest of hospitals in the health services provided by them, and working on continuous updating of them, given their important role in raising the efficiency and effectiveness of their performance.